WORK-LIFE BALANCE: A HISTORICAL REVIEW AND INSIGHTS FOR THE HOSPITALITY INDUSTRY - Knežević, Snežana; Gajić, Tamara; Sekulić, Dejan; Djoković, Filip; Vukolić, Dragan; Zrnić, Miloš (The Business of Tourism, 2023)
Work-life balance has become a popular area of research in the past twenty years. Before the 1970s, work and family were studied as mutually exclusive domains. The term "work-life balance" was introduced in the late 1970s to describe the balancing act of employed women who were mothers, juggling child care and work responsibilities. During the 1990s, the recognition of work-life balance’s significance emerged as a vital issue for all employees, regardless of gender, parental, or marital status. The concept of work-life balance has evolved from role conflict between family and work, managing multiple roles to work and life enrichment and integration. Currently, the goal of work-life balance research is to determine whether the expectations of employees regarding work and multiple life roles are compatible or not. The significance of work-life balance research extends to individual, organizational, institutional, and national levels of outcomes. It is particularly relevant in the hospitality sector due to the unique nature of the work involved (intense work activities, long working hours, challenges in human resource management, organization of work, vacation planning, a significant representation of women employees, and health issues among hospitality workers). Therefore, it is considered a crucial issue in the hotel industry.